Willingness to pay for birdsong - Anthony Higney; Charlotte Gerling; Claire Buchan; Simon Butler; Liam Crowther; Melissa Marselle; Eleanor Ratcliffe; Konrad Uebel; Nick Hanley (Ecological Economics, 2026)

Stable isotope evidence of plant water sources for alien and indigenous riparian trees in headwater streams, South Africa - Retang Anna Mokua; Paul Koeniger; Anthony Michael Swemmer; Rachel Keen; Mike Butler (Hydrological Sciences Journal, 2026)

Expanded methods for geometric location of 2D bone histology co-registration in 3D radiology volumes - Jaime Uy De Baron; Robert Phillips; Anthony Butler (Physical and Engineering Sciences in Medicine, 2026)
Bone sarcoma treatment employs wide surgical margins to ensure complete tumour excision, sometimes at the expense of patient quality of life. As precision technologies advance, quantitative data to inform the planned accuracy of surgical margins is increasingly important. This study assesses two novel computational methods (M2, M3) to support the co-registration of 2D histologic images within 3D radiological volumes. Replicated evaluation of an established method (M1) is also performed with new data. M2 suits concave bisected sections by assuming a different orientation during tissue bandsaw than M1. M3 handles freeform geometries by using a third measurement to constrain 2D histology images within 3D space without need for geometric bandsaw assumptions. Three computed distances across 38 canine specimen dissections from each method were compared with three corresponding physical measurements collected during laboratory processing. M1 produced a mean error of 0.12 (± 1.7) mm, M2 produced a mean error of 0.06 (± 1.9) mm, while M3 produced a mean error of 0.02 (± 1.5) mm. Mean errors for each method were of similar magnitude to 3D registration error reported in histology co-registration frameworks for other tissues. This study supports a simple low cost opportunity for use of digital histology images to support bone sarcoma radiology interpretation and treatment planning.

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

What is slowing progress on climate change adaptation? Evaluating barriers to planning for sea level rise in Florida - Anthony Charles Milordis; William Hale Butler; Tisha Joseph Holmes (Mitigation and Adaptation Strategies for Global Change, 2023)

Accounting for herbaceous communities in process‐based models will advance our understanding of “grassy” ecosystems - Kevin R. Wilcox; Anping Chen; Meghan L. Avolio; Ethan E. Butler; Scott Collins; Rosie Fisher; Trevor Keenan; Nancy Y. Kiang; Alan K. Knapp; Sally E. Koerner; Lara Kueppers; Guopeng Liang; et al. (Global Change Biology, 2023)
Grassland and other herbaceous communities cover significant portions of Earth's terrestrial surface and provide many critical services, such as carbon sequestration, wildlife habitat, and food production. Forecasts of global change impacts on these services will require predictive tools, such as process‐based dynamic vegetation models. Yet, model representation of herbaceous communities and ecosystems lags substantially behind that of tree communities and forests. The limited representation of herbaceous communities within models arises from two important knowledge gaps: first, our empirical understanding of the principles governing herbaceous vegetation dynamics is either incomplete or does not provide mechanistic information necessary to drive herbaceous community processes with models; second, current model structure and parameterization of grass and other herbaceous plant functional types limits the ability of models to predict outcomes of competition and growth for herbaceous vegetation. In this review, we provide direction for addressing these gaps by: (1) presenting a brief history of how vegetation dynamics have been developed and incorporated into earth system models, (2) reporting on a model simulation activity to evaluate current model capability to represent herbaceous vegetation dynamics and ecosystem function, and (3) detailing several ecological properties and phenomena that should be a focus for both empiricists and modelers to improve representation of herbaceous vegetation in models. Together, empiricists and modelers can improve representation of herbaceous ecosystem processes within models. In so doing, we will greatly enhance our ability to forecast future states of the earth system, which is of high importance given the rapid rate of environmental change on our planet.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Differential vulnerability of native and non-native mollusks to predation by juvenile black carp - Anthony P. Porreca; Steven E. Butler; Jeremy S. Tiemann; Joseph J. Parkos (Biological Invasions, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hares in the long grass: increased aircraft related mortality of the Irish hare (Lepus timidus hibernicus) over a 30-year period at Ireland’s largest civil airport - Samantha Ball; Fidelma Butler; Anthony Caravaggi; Neil E. Coughlan; Gerry Keogh; Michael J. A. O’Callaghan; Ricky Whelan; Thomas C. Kelly (European Journal of Wildlife Research, 2021)
Collisions between wildlife and aircraft are a serious and growing threat to aviation safety. Understanding the frequency of these collisions, the identity of species involved, and the potential damage that can be inflicted on to aircraft aid mitigation efforts by airfield managers. A record of all animal carcasses recovered from Dublin International Airport, Ireland’s largest civil aviation airport, has been maintained since 1990 where strikes with the endemic Irish hare ( Lepus timidus hibernicus ), a protected subspecies of mountain hare, are of particular concern despite substantial management efforts from the airfield authority. The first strike event with a hare was recorded in 1997, and strike events have substantially increased since then, with a sharp increase recorded in 2011. Over a 30-year period, a total of 320 strike events with the Irish hare have been recorded at the airfield. To date, no strike event with a hare has resulted in damage to an aircraft. However, carcasses can present as a major attraction to avian scavenger species in addition to posing as a risk of causing foreign object damage in the event of an undetected carcass. Hare strikes are discussed in the context of the rate of civil aircraft movements, possible direct and indirect damage to aircraft, and airfield wildlife hazard management. Here, we demonstrate that not only are strike events increasing by 14% on an annual basis, but that the kinetic energy of such an event has the potential to cause significant damage to an aircraft.

The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Faith Borgan; Katherine Beck; Emma Butler; Robert McCutcheon; Mattia Veronese; Anthony Vernon; Oliver D. Howes (Psychopharmacology, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Adaptation pathways: ecoregion and land ownership influences on climate adaptation decision-making in forest management - Todd A. Ontl; Chris Swanston; Leslie A. Brandt; Patricia R. Butler; Anthony W. D’Amato; Stephen D. Handler; Maria K. Janowiak; P. Danielle Shannon (Climatic Change, 2018)

Depleted Uranium Toxicity, Accumulation, and Uptake in Cynodon dactylon (Bermuda) and Aristida purpurea (Purple Threeawn) - Afrachanna D. Butler; Michelle Wynter; Victor F. Medina; Anthony J. Bednar (Bulletin of Environmental Contamination and Toxicology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Molecular and morphological insights into the origin of the invasive greater white-toothed shrew (Crocidura russula) in Ireland - Laura M. Gargan; Raphaël Cornette; Jon M. Yearsley; W. Ian Montgomery; Joana Paupério; Paulo C. Alves; Fidelma Butler; Michel Pascal; Anne Tresset; Anthony Herrel; John Lusby; David G. Tosh; et al. (Biological Invasions, 2016)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

Scaffolds for Tendon and Ligament Repair and Regeneration - Anthony Ratcliffe; David L. Butler; Nathaniel A. Dyment; Paul J. Cagle; Christopher S. Proctor; Seena S. Ratcliffe; Evan L. Flatow (Annals of Biomedical Engineering, 2015)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Estimation of spawning habitats of market squid ( Doryteuthis opalescens ) from field surveys of eggs off Central and Southern California - Louis D. Zeidberg; John L. Butler; Darlene Ramon; Anthony Cossio; Kevin L. Stierhoff; Annette Henry (Marine Ecology, 2012)
Like many other loliginid squid, Doryteuthis (Loligo) opalescens deposits egg cases on the ocean floor. Depending upon temperature, egg cases may persist for 5–12 weeks before the paralarvae hatch. Because of this relatively long duration and squid’s pelagic life history, egg cases provide a practical life stage to survey. During 2001–2002, squid egg beds in Monterey Bay, Carmel Bay, and around the California Channel Islands were surveyed using a remotely operated vehicle with the goal of delineating the habitat of egg beds that are spawned during active commercial fishing. Egg cases were highly aggregated and densities reached 1338 capsules m −2 . Squid eggs were significantly shallower in Central California. Egg cases occurred between 20 and 93 m around the Channel Islands, and in Central California they were between 13 and 61 m. The temperatures in both regions were similar (10–12 °C), with some eggs in Southern California found up to 14.4 °C. Ninety‐five percent of eggs were found on sand, suggesting that temperature and substrate are stronger behavioral cues than depth to stimulate spawning. Suitable spawning habitat was defined by three criteria: sandy benthic substrate, temperatures between 10 and 14.4 °C, and depths between 20 and 70 m when the first two criteria hold. Additionally, within this defined area, oxygen concentration is quantified. The greatest commercial landings of market squid occur in both Central and Southern California during a time of year when water temperatures of 10–12 °C are prevalent in the 20–70 m depth range.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’ - Jonathan A. Green; Rory P. Wilson; Ian L. Boyd; Anthony J. Woakes; Chris J. Green; Patrick J. Butler (Polar Biology, 2009)

Invertebrate community variation in seasonal forest wetlands: Implications for sampling and analyses - Anthony T. Miller; Mark A. Hanson; James O. Church; Brian Palik; Shane E. Bowe; Malcolm G. Butler (Wetlands, 2008)

Expression of cry1Ac9 and cry9Aa2 genes under a potato light-inducible Lhca3 promoter in transgenic potatoes for tuber moth resistance - Sathiyamoorthy Meiyalaghan; Jeanne M. E. Jacobs; Ruth C. Butler; Steve D. Wratten; Anthony J. Conner (Euphytica, 2006)